An Interesting Suicide Method a Case Report - Demirkıran, Dua Sumeyra; Çelikel, Adnan; Zeren, Cem; Arslan, Muhammet Mustafa (The Bulletin of Legal Medicine, 2014)
The aim of this study is to present a case who committed suicide by an incomplete hanging method. A woman, who was 80 years old with low-socioeconomic-status and living alone, was found dead at home. There was history of medicine usage for psychiatric problems. In crime scene investigation, there was blood trail in different parts of kitchen, room and courtyard and also a washtub with blood and a bread knife inside was found. The case was found hanged to the wall side metal of the stretcher with a woman sock. The distance between the knot and the ground was measured as 20cm. In external examination there was ligature mark on neck, numerous cutting wounds in anterior side of both wrists and posterior side of left wrist and hand. There were no trauma signs at body other than the ligature mark and the cutting wounds. It was understood that the case was died as a result of asphyxia due to hanging. We are presenting this case because she was carrying risk factors for suicide, usage of two different methods for suicide and strangeness of hanging method.Keywords: Suicide, Old age, Two different suicide method.
Keywords: suicide; old age; two different suicide method